Relationship Model for Occupational Safety and Health Climate to Prevent Needlestick Injuries for Nurses - Ismara, Ketut Ima; Husodo, Adi Heru; Prabandari, Yayi Suryo; Hariyono, Widodo (Kesmas, 2019)
The risk of accidents and disease transmission when working at hospitals is quite high, especially in Indonesia. This study aimed to analyze the relationship model between the Occupational Safety and Health (OSH) climate and behavior intention in OSH performance to prevent needlestick injuries (NSI) based on a theory of planned behavior. A mixed approach using qualitative and quantitative methods was applied. Data were obtained from Structural Equation Model questionnaires, observation, and documentation, and interviews were analyzed qualitatively. The population was 1,042 nurses at Dr. Sardjito General Hospital in Yogyakarta. The sample consisted of 289 respondents determined by purposive random sampling with an accuracy level of 5%. The OSH climate consisted of attitude, norm, and perceived behavioral control effect on safety intention. An indirect OSH climate can influence safety performance, but it must be followed by intention. Intention directly affects safety performance in the form of behavior to implement NSI prevention procedures. Attitudes toward risk, attitudes toward leader commitment as role models, group norms, and beliefs in the ability to perform safety and health procedures determine the safety climate that leads to the intention for safe and healthy behavior in OSH performance.